2021
DOI: 10.1017/hpl.2021.29
|View full text |Cite
|
Sign up to set email alerts
|

Efficient bright γ-ray vortex emission from a laser-illuminated light-fan-in-channel target

Abstract: X/γ-rays have many potential applications in laboratory astrophysics and particle physics. Although several methods have been proposed for generating electron, positron, and X/γ-photon beams with angular momentum (AM), the generation of ultra-intense brilliant γ-rays is still challenging. Here, we present an all-optical scheme to generate a high-energy γ-photon beam with large beam angular momentum (BAM), small divergence, and high brilliance. In the first stage, a circularly polarized laser pulse with intensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 77 publications
0
8
0
Order By: Relevance
“…An ingenious, all-optical scheme based on non-linear Compton backscattering was recently proposed in [182]. An extremely intense circularly polarized laser pulse irradiates a micro-channel target, drags out electrons from the channel wall, accelerates them to high energies (hundreds of MeV) and, at the same time, transfers its spin angular momentum to this electron beam.…”
Section: Vortex States Colliding With Ion Beamsmentioning
confidence: 99%
See 4 more Smart Citations
“…An ingenious, all-optical scheme based on non-linear Compton backscattering was recently proposed in [182]. An extremely intense circularly polarized laser pulse irradiates a micro-channel target, drags out electrons from the channel wall, accelerates them to high energies (hundreds of MeV) and, at the same time, transfers its spin angular momentum to this electron beam.…”
Section: Vortex States Colliding With Ion Beamsmentioning
confidence: 99%
“…Upon reflection, this intense vortex light pulse collides with the energetic electron pulse and gets upscattered into the MeV energy range, taking a very large OAM from the electrons. The very detailed numerical study reported in [182] was based on the 3D particle-in-cell simulations, with QED effects computed via a Monte Carlo algorithm, which included radiation reaction and the feedback between the plasma and photon emission. The parameters of the pulse were chosen to ensure a moderately non-linear regime for the Compton scattering, with ξ = 0.55.…”
Section: Vortex States Colliding With Ion Beamsmentioning
confidence: 99%
See 3 more Smart Citations